PERBEDAAN PENGETAHUAN, SIKAP, DAN KONSUMSI MAKANAN DAN MINUMAN INSTAN PADA REMAJA DENGAN STATUS GIZI LEBIH DAN STATUS GIZI NORMAL DI SMA MUHAMMADIYAH 1 YOGYAKARTA - , FANNY WIDYA PRATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Advances in science and technology in the food industry to encourage the emergence of instant products, such as food and instant drinks (Lastariwati, 2006). Effect on the level of nutritional knowledge attitudes and behaviors in the selection of food (Irawati et al, 1992). Knowledge of good nutrition will also influence the pattern of food intake more healthy (Fitzgerald et al, 2008). Basically, food consumption will affect the nutritional status. Objectives : To find the difference between knowledge, attitudes, and consumption of instant food and beverages in adolescents with better nutritional status and normal nutritional status at SMA Muhammadiyah 1 Yogyakarta. Methods : This research was an observational study with case-control design. The subjects were 114 people (38 case and 76 control). The statistical test used is chi square test and uji fisherâs exact test. Results : Sufficient level of knowledge, higher in the case group (7,9%) than the control group (6,6%), while a good level of knowledge (92,9%), higher in the control group (93,4%) than the case group (92,1%). Attitude in enough categories, higher in the control group (11,8%) than the case group (10,5%), while a good level of attitude (88,6%), higher in the case group (89,5%) than the control group (88,2%). Consumption of instant food and beverages in more categories, higher in the control group (51,3%) than the case group (23,7%), while the category is quite, higher in the case group (76,3%) than the control group (48,7%). Conclusions : There is no difference in knowledge and attitudes about food and instant drinks in adolescents with better nutritional status and normal nutritional status, but there are difference in the consumption of instant food and beverage in adolescents with better nutritional status and normal nutritional status.